A Metric Fractionator for Estimation of Total Cell Number in Paraffin-Embedded Flat or Hollow Organs. (August 2020) - Mirabile, Rosanna; Boyce, Rogely Waite; Gundersen, Hans Jørgen G.
The physical fractionator is a convenient and practical solution for estimation of total cell number in a regulatory toxicology setting because it is insensitive to shrinkage allowing for paraffin processing/embedding and does not require measurement of the reference or organ volume. The principle involves sampling a known fraction of an organ in one or more steps and counting the total number of cells present in the final sample, physical disector section pairs. The total cell number in the organ is estimated by multiplying the cell count in the final fraction by the inverse of the sampling fraction(s). The key feature of the design is that tissue shrinkage due to paraffin processing occurs before the organ is uniformly sampled. Another requirement is that thermal expansion or contraction is avoided during the preparation of disector sections from the individual embedded subsamples, which ensures that the disector sections represent a known constant fraction. This vertical physical fractionator with subsampling is a simple and fast estimator to obtain precise and robust estimates of total cell number in large flat or hollow organs that do not prolong routine necropsy procedures. It is compatible with paraffin processing, avoids exhaustive sectioning, and allows for the collection of routine histopathology sections.